2013
DOI: 10.5483/bmbrep.2013.46.6.121
|View full text |Cite
|
Sign up to set email alerts
|

Acid-sensing ion channels (ASICs): therapeutic targets for neurological diseases and their regulation

Abstract: Extracellular acidification occurs not only in pathological conditions such as inflammation and brain ischemia, but also in normal physiological conditions such as synaptic transmission. Acid-sensing ion channels (ASICs) can detect a broad range of physiological pH changes during pathological and synaptic cellular activities. ASICs are voltage-independent, proton-gated cation channels widely expressed throughout the central and peripheral nervous system. Activation of ASICs is involved in pain perception, syna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
75
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(75 citation statements)
references
References 109 publications
0
75
0
Order By: Relevance
“…It is known that the local extracellular pH levels drop to 5.4 in acute inflammation and 6.3 or lower in severe ischemia [13,14]. The released protons can cause pain through activating protongated ion channels on peripheral sensory afferents.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that the local extracellular pH levels drop to 5.4 in acute inflammation and 6.3 or lower in severe ischemia [13,14]. The released protons can cause pain through activating protongated ion channels on peripheral sensory afferents.…”
Section: Introductionmentioning
confidence: 99%
“…Provocative evidence has demonstrated that ASICs, which are known to be activated by extracellular H ϩ , are novel targets for ischemic stroke therapy (51)(52)(53). In contrast to the decrease in extracellular pH with focal ischemia, intracellular pH changes and specifically an increase of intracellular pH have been reported in many studies (27,29,31,32,54).…”
Section: Discussionmentioning
confidence: 99%
“…These toxins, as well as a toxin from the Texas coral snake (Micrurus tener tener) known as MitTx, are of interest because they belong to a family of toxins that specically affect acid-sensing ion channels (ASICs), which are key mediators of inammatory pain. 190 MitTx, however, induces hyperalgesia in animals. 191 Because these toxins affect ASICs, they hold the potential for development as analgesics targeting many different localized types of pain.…”
Section: Analgesicsmentioning
confidence: 97%